Effect of Cd–Zn compound contamination on the physiological response of broad bean and aphids - Chen, Liya; Wan, Sijing; Shen, Qintian; Zhao, Keting; He, Yanlan; Xie, Yexin; Tao, Shiyu; Zheng, Shuchang; Zhang, Yi; Wang, Shigui; Tang, Bin; Li, Yan (Frontiers in Physiology, 2025)
IntroductionThe heavy metal elements cadmium (Cd) and zinc (Zn) often coexist in nature, making the environmental media more prone to compound pollution. However, research on the toxic effect of the Cd–Zn combination is still lacking, and the underlying toxic mechanisms remain unclear.MethodsTherefore, in this experiment, we established four treatment groups with different ratios of Cd–Zn compound stress for the broad bean, Vicia faba L., and aphids, Megoura crassicauda, to explore the growth and physiological adaptation mechanisms under different levels of mixed heavy metal stress.ResultsBy measuring the germination rate, seedling height, and chlorophyll content of broad beans, we found that Cd–Zn-mixed stress has a synergistic inhibitory effect on the growth and development of broad beans. Cd and Zn can be transferred through the food chain, while broad beans can resist complex stress by regulating the content of total soluble sugars and photosynthetic pigments in the body, as well as accumulating proline. In addition, in the first generation of adult aphids, treatment with Cd (12.5 mg/kg) + Zn (100 mg/kg) significantly affected the expression of trehalase (TRE) and trehalose-6-phosphate synthase (TPS) genes and influenced the carbohydrate content and trehalase activity in the aphids.DiscussionThe number of offspring produced by the second-generation aphids was significantly reduced under mixed heavy metal treatment, but it was not caused by changes in the vitellogenin (Vg) content. These related results provide new avenues for further exploration of plant responses to mixed heavy metal stress, pest control, and management of heavy metal pollution.